Enhancement of evaluation methodologies for natural fiber composites material selection system - Faris Al-Oqla, Faris Mohammed Khair (2015)
Proper evaluations of natural fiber composites (NFCs) and their constituents are of paramount importance in making informative decisions toward enhancing their selection process for future sustainable design possibilities. Consequently, this study was conducted to develop evaluation methodologies and selection models to properly evaluate and develop the selection system of the NFCs and their constituents as well as to discover new potential natural fiber types capable for improving the NFCs’ desirable characteristics. Hence, this study started with identifying the gap in evaluating the available natural fiber types relative to comprehensive desired criteria, then building a categorization framework to categorize and classify criteria that affect NFCs and their products into appropriate levels. Five distinguished levels were introduced as a primary evaluation tool for designers in this field. Moreover, the feasibility of using the date palm fiber (DPF) type in NFCs for automotive industry was investigated utilizing selected criteria from the presented levels. In contrast, a combined multi-criteria evaluation stage technique (CMCEST) was also introduced as a new systematic, simple and efficient indicator to enhance better evaluations of the available natural agro wastes for polymeric-based composites. In the proposed technique, sequence of evaluation stages where introduced as: single-evaluation-criterion (SEC), combined-doubleevaluation-criterion (CDEC), combined-triple-evaluation-criterion (CTEC), etc. The CMCEST enhancements can reveal new potential fiber types through better evaluation schemes. Furthermore, this work developed and introduced a novel systematic evaluation methodology for natural fibers’ capabilities based on moisture content criterion (MCC). This MCC evaluation tool was designed to predict the behavior of the available natural fibers regarding distinctive desirable characteristics under the effect of the moisture absorption phenomenon. MCC is capable of enhancing the selection process of NFCs for better sustainable design possibilities. In addition, efforts were integrated to enhance and develop the selection process of NFCs’ constituents to achieve a real novel progress in this field. Thus, a decision making model was developed to rank and evaluate various available polymers to determine the most appropriate polymer matrix type for natural fiber composites considering twenty different criteria standpoints simultaneously. Moreover, this study also developed decision-support models to evaluate and select the optimal reinforcement conditions of the Date Palm/Epoxy composite to maximize its overall tensile property considering combined evaluation criteria. The usefulness of the developed evaluation methodologies and models was successfully demonstrated through their capabilities in enhancing better evaluations of the NFCs regarding wide range of multiple conflicting criteria as well as eliminating the bias or prejudice in decisions and reduce human errors in the selection process.